Influence of maturity stage at harvest and ethylene application on colour and quality of controlled atmosphere-stored mango fruit - Dang, Khuyen; Singh, Zora; Tan, S. (Interntional Society Horticultural Science, 2008)
Short storage life of mango (Mangifera indica L.) fruit limits its export to distant markets. Sea transport of mango is more economical but requires a longerperiod of transportation than airfreight. Controlled atmosphere (CA) storage extends shelf life of ‘Kensington Pride’ mango, a major commercial mango cultivar grown in Australia. Storing mango fruit under CA conditions often results in poor colour development of ripe fruit. Effects of fruit maturity and ethylene treatment on fruit colour and quality of CA-stored mango were investigated. Fruit at two different maturities (hard mature green and sprung) were harvested and stored in CA chambers containing 2% O2 and 5% CO2 (balance N2) at 13±0.5°C and 85±3% RH. After three or five weeks in CA, mangoes were removed and treated with 0, 50, 100 or 150 μl·L-1 ethylene in closed containers for twelve continuous hours, then allowed to ripen at 21±0.5°C until eating ripe stage. Ripening and fruit quality attributes such as ripening time, respiration rate, fruit colour development, and concentrations of soluble solids, titratable acidity, vitamin C, and total carotenoids were measured. Fruit harvested at sprung stage had better colour and carotenoid concentration, regardless of CA storage duration and ethylene concentration applied, than those harvested at the hard mature stage. Longer CA storage induced adverse effects on fruit colour development, titratable acidity, vitamin C, and total carotenoids concentration. Post CA storage ethylene application had little effect on fruit colour and quality. In conclusion, following CA storage, fruit harvested at sprung maturity stage exhibited better colour development and carotenoids than fruit harvested at the hard mature green stage irrespective of ethylene treatments.